Cuticular hydrocarbons of Chagas disease vectors in Mexico - Juárez, Marta Patricia (2002)
Capillary gas-liquid chromatography was used to analyse the cuticular hydrocarbons of three triatomine species, Triatoma dimidiata, T. barberi and Dipetalogaster maxima, domestic vectors of Chagas disease in Mexico. Mixtures of saturated hydrocarbons of straight and methyl-branched chains were characteristic of the three species, but quantitatively different. Major methylbranched components mostly corresponded to different saturated isomers of monomethyl, dimethyl and trimethyl branched hydrocarbons ranging from 29 to 39 carbon backbones. Sex-dependant, quantitative differences in certain hydrocarbons were apparent in T. dimidiata.